PENGARUH KNOWLEDGE MANAGEMENT TERHADAP KINERJA SUMBER DAYA MANUSIA DENGAN ARTIFICIAL INTELLIGENCE SEBAGAI VARIABEL MODERASI DI PT. TELEKOMUNIKASI SELULAR WILAYAH SURABAYA - Riyadus Solihin; Akhmad Fauzi; Eko Purwanto (ITB AAS Indonesia Surakarta, 2023)
Knowledge Management has an important role in a company as a supporter in company development. By utilizing artificial intelligence, Knowledge Management practices can be improved in a significant way so as to be able to connect and combine knowledge across various systems so as to assist employees in sharing and processing knowledge. This study aims to determine the influence of Knowledge Management on human resource performance moderated by Artificial Intelligence at PT. Cellular Telecommunications (Telkomsel) Surabaya area. This research uses quantitative methods. The population in this study is all employees at GraPARI Telkomsel Surabaya area who deal directly with customers, master product knowledge, such as serving information, requests and complaints for services for all Telkomsel customers, namely Customer Service and Marketing. The sample used in this study was 41 GraPARI Telkomsel Surabaya employees. The research data was obtained from the results of filling out a questionnaire with a 5-point likert scale and analyzed using the SEM PLS analysis technique with the help of the SmartPLS program. The results of this study prove that (1) Knowledge Management has a role in improving human resource performance, the better the level of Knowledge Management will make employee performance higher, in this case employees who have work experience in their fields play an important role in Knowledge Management in Transfer such knowledge to other employees to improve employee performance. (2) The results of this study prove that Artificial Intelligence moderates the role of Knowledge Management on human resource performance, in this case Artificial Intelligence is able to automate some repetitive work so as to increase the efficiency of employee performance to focus more on handling more complex problems. Keywords : Knowledge Management, artificial intelligence, HR performance